Features of the ecology of Rhinolophus mehelyi (Chiroptera: Rhinolophidae) during hibernation in the north‐east of the Caucasus - A. V. Zhigalin; A. A. Gadzhiev; B. A. Mutashev; A. Yu. Alekseev (Юг России: экология, развитие)
The cave was surveyed and the animals were counted 1–2 times a month. Microclimatic indicators were recorded by automatic loggers.During the research, it was found that the place of hibernation of R. mehelyi in the north‐east of the area is the Karabudakhkentskaya Cave. The minimum, maximum and average temperatures in the cave during the wintering period of R. mehelyi are equal: 6.9 oC, 15.6 oC and 12.4 oC accordingly. The minimum humidity was 89.1 %, the maximum was 98.2 % and the average was 92.7 %. It was found that the temperature inside the shelter affects the number of individuals in the visible part of the cave and the formation of individual groupings. In addition, there is an increase in the number of individuals in April before the start of migration.It was found that humidity does not affect the movement of the species inside the cave, but temperature is a factor determining the movement of animals and their crowding. Thus, to accurately record the number of species, which is important for carrying out environmental measures, it is necessary to take into account both indicators – temperature and time of research.